1. Упростить выражения:
а) (х-12)(х+12)
б) ( 3а+ 2b) (2b- 3a)
в) (n-4n3) ( n+ 4n3)
г) (5a+0,2)(0,2 - 5a)
д) (- 6a - 2b) (6a - 2b)
е) (b2+ 4) (b- 2) (b+2)
2. Разложить на множители.
а) y2- 100
б) -0,16 x2+ y2
в) a4 - 25
г) 400- y2
д) - 0,25 x2+ y2 z2
е) (x+1)2 - 4

  • 1.
    а) (х-12)(х+12)=х^2+12x-12x-144=x^2-144
    б) ( 3а+ 2b) (2b- 3a)=6ab-6a^2+4b^2-6ab=6a^2+4b^2
    в) (n-4n3) ( n+ 4n3)=n^2+4n^4-4n^4-16n^6=n^2-16n^6
    г) (5a+0,2)(0,2 - 5a)=a-25a^2+0.04-a=25^2+0.04
    д) (- 6a - 2b) (6a - 2b)=-36a^2+12ab-12ab+4b^2=-36a^2+4b^2